2021
DOI: 10.1007/s11548-021-02307-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual fluoroscopic imaging and CT-based finite element modelling to estimate forces and stresses of grafts in anatomical single-bundle ACL reconstruction with different femoral tunnels

Abstract: Purpose Little is known about the in vivo forces and stresses on grafts used in anterior cruciate ligament (ACL) reconstruction. The aims of this study were to evaluate and compare the forces and stresses on grafts used in anatomical single-bundle ACL reconstruction at different locations of the femoral footprint (anterior vs middle vs posterior; high vs middle vs low) during a lunge motion. Methods Establish subject-specific finite element models with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Furthermore, the maximum strain exceeding 4000 μ‐strain occurred around the P zone of the entrance of tibial tunnel. Lind et al 33 showed the femoral tunnel widening was more severe than tibial tunnel widening, which was consistent with the results of the present study, where the stress concentration was higher at the femoral side. Moreover, Fink et al 34 found that tibial tunnel enlargement in the sagittal plane was larger than that in the coronal plane.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the maximum strain exceeding 4000 μ‐strain occurred around the P zone of the entrance of tibial tunnel. Lind et al 33 showed the femoral tunnel widening was more severe than tibial tunnel widening, which was consistent with the results of the present study, where the stress concentration was higher at the femoral side. Moreover, Fink et al 34 found that tibial tunnel enlargement in the sagittal plane was larger than that in the coronal plane.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies 14,18,33,35 have showed the highest contact stress occurred at the femoral graft contact region when the ACL graft wrapped over the sharp entrances of the tunnels. Bae et al 18 reported that distributed regions of contact pressure occurred around the impingement site between the femoral tunnel entrance and the graft with AM portal and transtibial technique.…”
Section: Discussionmentioning
confidence: 99%
“…Hoshino et al in their cadaveric study, reported that different mechanical stress around the femoral tunnel was exhibited according to different directions [ 14 ]. Recent Finite element studies have demonstrated that the contact stress arising at the interface between the graft and the surrounding bony structures was influenced by different femoral tunnel positions, and changes in the reaction force and maximal stress of the graft was also affected by knee motion [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different trajectories of the ACL graft could yield different tunnel parameters including length of the femoral tunnel and femoral graft bending angle [9][10][11][12][13]. Different tunnel parameters are consequently associated with different stress patterns around the femoral tunnel [14][15][16][17][18]. Hoshino et al in their cadaveric study, reported that different mechanical stress around the femoral tunnel was exhibited according to different directions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Does single bundle reconstruction have better anatomic AM selection? [8][9][10][11][12] Alternatively, is it better to choose the anatomic mid-bundle (the center of the femoral footprint)? [13][14][15] The current literature does not yet provide uniform conclusions [16].…”
mentioning
confidence: 99%